The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1476-5381.1989.tb11986.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for prazosin‐resistant, rauwolscine‐sensitive α‐adrenoceptors mediating contractions in the isolated vascular bed of the rat tail

Abstract: 1 The postjunctional x-adrenoceptors mediating contractions in the isolated vascular bed of the perfused rat tail have been investigated, in the presence and absence of an increase in perfusion pressure by arginine vasopressin (AVP). 2 In the absence of AVP, bolus doses of noradrenaline (NA) and phenylephrine produced pressor responses of similar time course, while UK-14,304 was practically inactive. Responses to noradrenaline were inhibited more by 0.05 yM prazosin than by 1 yM rauwolscine, suggesting the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1989
1989
1995
1995

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…We have previously shown that, in order to observe responses mediated by post-junctional x2-adrenoceptors, vascular tone must be increased. For example, in the rat tail artery, when vascular tone is raised with vasopressin, endothelin-1 or 5-hydroxytryptamine, a previously quiescent a2-adrenoceptor population is uncovered (Templeton et al, 1989;MacLean & McGrath, 1990). In addition, inhibition of neuronal uptake will reveal z2-adrenoceptor-mediated nerve responses in the rat tail artery (Papanicolaou & Medgett, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that, in order to observe responses mediated by post-junctional x2-adrenoceptors, vascular tone must be increased. For example, in the rat tail artery, when vascular tone is raised with vasopressin, endothelin-1 or 5-hydroxytryptamine, a previously quiescent a2-adrenoceptor population is uncovered (Templeton et al, 1989;MacLean & McGrath, 1990). In addition, inhibition of neuronal uptake will reveal z2-adrenoceptor-mediated nerve responses in the rat tail artery (Papanicolaou & Medgett, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…For example it has been reported that the expression of postjunctional CX2-adrenoceptor-mediated responses to UK-14304 in the rabbit distal saphenous artery is dependent upon the presence of angiotensin II (All) (Dunn et al, 1989). Similarly, in the perfused isolated tail of the rat a2-adrenoceptor-mediated responses are observed only after raising tone with, for example vasopressin or endothelin (Templeton et al, 1989;MacLean & McGrath, 1990), while in the canine saphenous artery a non-contractile concentration of Bay K 8644 allowed the demonstration of responses mediated by the subtype (Sulpizio & Hieble, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even though no functional response was observed in this vessel, M2-adrenoceptor binding sites were detected and they appear to be located almost exclusively on the smooth muscle. We are currently examining the possibility that a2-adrenoceptor-mediated contraction in the splenic artery can be uncovered by the presence of an ancillary spasmogen, as previously described in the rat isolated tail artery (Templeton et al, 1989) and rabbit isolated distal saphenous artery (Dunn et al, 1991).…”
Section: Saturation Studies In Other Porcine Blood Vesselsmentioning
confidence: 99%
“…The KrebsHenseleit saline was maintained at 31 C for the ear vein, and at 37TC for the SA and TA, and gassed with 95%02/5%CO2. The superficial blood vessels were maintained at 31 C because previous studies have shown that M2-adrenoceptor function is enhanced at lower temperature (Flavahan & Vanhoutte, 1986;Templeton et al, 1989). No attempt was made to remove the endothelium.…”
Section: Functional Studiesmentioning
confidence: 99%